MiR-379-5p aggravates experimental autoimmune uveitis in mice via the regulation of SEMA3A - Mohan Li; Xiang Gao; Kou Liu; Ning Bao; Zhengxuan Jiang (Taylor & Francis Group, 2021)
Uveitis is a disease resulting in the inflammation of uveal tracts, but the factors resulting in uveitis is still obscure. Previous studies have shown that miR-379-5p was involved in the pathogenesis of several diseases, however, the role and regulatory mechanism of miR-379-5p in uveitis were unclear. In our study, we established experimental autoimmune uveitis (EAU) mouse models to explore the role of miR-379-5p in uveitis. RT-qPCR identified that miR-379-5p level was increased in serum of EAU mice. In mechanism, SEMA3A 3'UTR was proven to be directly targeted by miR-379-5p and SEMA3A expression was negatively regulated by miR-379-5p in CD4+ T cells. Moreover, ELISA analysis revealed that knockdown of miR-379-5p suppressed the production of inflammation cytokines including IL-17, TNF-α and IL-β in vitro. These results were reversed by SEMA3A overexpression. In addition, the reduction of Th17 cells under miR-379-5p inhibitor was neutralised by SEMA3A knockdown in vitro. Furthermore, we demonstrated that knockdown of miR-379-5p significantly reversed the increased clinical scores and inflammatory response resulting from EAU treatment and this effect was further countervailed by SEMA3A silencing. Our study suggested that miR-379-5p aggravated uveitis in EAU mice via the regulation of SEMA3A, which may provide a novel insight for uveitis treatment.